2015
DOI: 10.1002/anie.201503968
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Ligation and Isotope Labeling to Locate Dynamic Effects during Catalysis by Dihydrofolate Reductase

Abstract: Chemical ligation has been used to alter motions in specific regions of dihydrofolate reductase from E. coli and to investigate the effects of localized motional changes on enzyme catalysis. Two isotopic hybrids were prepared; one with the mobile N‐terminal segment containing heavy isotopes (2H, 13C, 15N) and the remainder of the protein with natural isotopic abundance, and the other one with only the C‐terminal segment isotopically labeled. Kinetic investigations indicated that isotopic substitution of the N‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 45 publications
3
71
0
Order By: Relevance
“…33 However, these studies show different effects of isotopic substitution depending on the enzymatic system. Beyond assessing the importance of protein dynamics in enzyme catalysis 34-36 heavy enzyme studies have also been used in the development of inhibitors for pharmaceutical applications as well. 37,38 Nevertheless, further investigation is vital to obtain a comprehensive understanding of the correlation between altered fast protein dynamics and the catalyzed reaction along with other effects of isotopic substitution on enzyme catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…33 However, these studies show different effects of isotopic substitution depending on the enzymatic system. Beyond assessing the importance of protein dynamics in enzyme catalysis 34-36 heavy enzyme studies have also been used in the development of inhibitors for pharmaceutical applications as well. 37,38 Nevertheless, further investigation is vital to obtain a comprehensive understanding of the correlation between altered fast protein dynamics and the catalyzed reaction along with other effects of isotopic substitution on enzyme catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent examples include ubiquitin 36 , alpha-synuclein 37 , histones 38 , and membrane proteins 39 . Additional examples include fundamental ubiquitin biology 40 , proteins with selective isotopic labeling 41 , site-specific installation of fluors (e.g., FRET pairs) 42 , and interesting scaffold approaches 43 .…”
Section: Introductionmentioning
confidence: 99%
“…These apparently contradictory results demonstrate the delicate nature of motional coupling to catalysis. We have refined this global picture of motional coupling by isotopically labeling specific segments of an enzyme and therefore experimentally determining which parts of the enzyme show motional coupling [19]. Two isotopic hybrids of DHFR were prepared by chemical ligation techniques [20], one in which the mobile N-terminal segment contained heavy isotopes while the remainder of the protein was of natural isotopic abundance, and one in which only the C-terminal region was isotopically labeled.…”
mentioning
confidence: 99%
“…Two isotopic hybrids of DHFR were prepared by chemical ligation techniques [20], one in which the mobile N-terminal segment contained heavy isotopes while the remainder of the protein was of natural isotopic abundance, and one in which only the C-terminal region was isotopically labeled. These experiments revealed that the N-terminal region is only involved in beneficial millisecond conformational motions, while in the C-terminal region fast dynamic motions couple unfavorably to barrier crossing, thereby slowing the reaction [19]. The combination of chemical ligation and heavy enzyme approaches has shown for the first time that different parts of an enzyme affect different aspects of its function.…”
mentioning
confidence: 99%